Exploring the publication gap in pediatric randomized clinical trials: completed vs. uncompleted pediatric clinical trials - Nebeska, Katerina; Souckova, Lenka; Stepanova, Radka; Demlova, Regina (Frontiers in Medicine, 2025)
BackgroundRandomized clinical trials (RCTs) are essential for advancing medical knowledge, especially in pediatrics, where they provide critical evidence for safe and effective treatments. Regulatory frameworks like the Pediatric Regulation in the EU and the Best Pharmaceuticals for Children Act in the U.S. have spurred growth in pediatric RCTs. However, these clinical trials face unique challenges, including ethical complexities, recruitment difficulties, and funding limitations, which can hinder their completion. The publication of RCTs’ results is equally crucial, yet not all completed RCTs share their findings, contributing to publication bias. This bias, especially in pediatric clinical trials, can distort medical evidence, impact clinical decisions, and potentially compromise patient safety.MethodsWe conducted a cross-sectional analysis of pediatric RCTs registered on ClinicalTrials.gov between 2011 and 2013, with completion status by 2017. Inclusion criteria included clinical trials with drug interventions in participants aged 0-17 and randomization. Data on RCTs characteristics, including phase, funding source, participant age, and enrollment, were extracted. RCTs completion status was assessed, and reasons for incompletion were categorized. Publication status was evaluated through registry and manual searches on PubMed and Google Scholar. Statistical analyses, including logistic regression, were performed to identify factors associated with trial incompletion and non-publication.ResultsOut of 2875 pediatric clinical trials reviewed, 1088 met the inclusion criteria. Among these, 16.54% were uncompleted, primarily due to patient accrual issues (32.22%). Academic sponsors funded 48.53% of trials, and industrial sponsors funded 45.13%. Of 908 completed RCTs, 58.48% posted results in registries, while 70% had results published in peer-reviewed journals. Industrially funded RCTs were more likely to post results, but academic RCTs had a higher scientific publication rate. The median time to first result publication in registries was 21 months, with significant delays linked to the trial phase, funding, and participant enrolment size.ConclusionOur study highlights significant challenges in pediatric RCTs, including high incompletion rates and delays in result reporting. Ethical, regulatory, and logistical barriers hinder progress, impacting evidence transparency. Strengthened regulatory oversight and enhanced compliance are essential to improve pediatric research outcomes and ensure timely dissemination of RCTs results.